2014
DOI: 10.3390/md12041773
|View full text |Cite
|
Sign up to set email alerts
|

Peridinin from the Marine Symbiotic Dinoflagellate, Symbiodinium sp., Regulates Eosinophilia in Mice

Abstract: Peridinin and fucoxanthin, which are natural carotenoids isolated from a symbiotic dinoflagellate, Symbiodinium sp., and a brown alga, Petalonia fascia, respectively, were compared for inhibitory effects on delayed-type hypersensitivity in mice. The number of eosinophils at the site of inflammation and in peripheral blood was compared for the administration of peridinin and fucoxanthin applied by painting and intraperitoneally. Peridinin, but not the structurally-related fucoxanthin, significantly suppressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Peridinin and fucoxanthin, carotenoids isolated from Symbiodinium sp., a symbiotic dinoflagellate, and from Petalonia fascia, a brown alga, respectively, were shown to suppress allergic inflammatory responses through the inhibition of delayed-type hypersensitivity in mice, and to reduce the number of eosinophils in both the ear lobe and peripheral blood. The inhibitory effect of peridinin was higher than that of fucoxanthin [144].…”
Section: Cytokine Levels 421 Th2 Cytokinesmentioning
confidence: 76%
“…Peridinin and fucoxanthin, carotenoids isolated from Symbiodinium sp., a symbiotic dinoflagellate, and from Petalonia fascia, a brown alga, respectively, were shown to suppress allergic inflammatory responses through the inhibition of delayed-type hypersensitivity in mice, and to reduce the number of eosinophils in both the ear lobe and peripheral blood. The inhibitory effect of peridinin was higher than that of fucoxanthin [144].…”
Section: Cytokine Levels 421 Th2 Cytokinesmentioning
confidence: 76%
“…Metabolites 7 and 8 showed 65% and 32% cyclooxygenase-2 inhibition at 2 and 10 μM concentrations, respectively [52,53]. Compound 23 was evaluated basis its ability to suppress delayed-type hypersensitivity in mice [44]. Metabolite 10 has been reported to inhibit L-phosphatidylserine-stimulated protein kinase C activity [54].…”
Section: Biologically Activementioning
confidence: 99%
“…Owing to this property, it is currently used as a fluorescent dye in flow cytometry [80]. e study reported producing this compound in a 132 L culture for more than 40 days [44], with a yield of 24.7 mg (Table 3). However, using the immobilized approach and after 28 days of culture, approximately 1 g of peridinin was produced from the S. voratum CCAC 0047 strain [81].…”
Section: Challenges Related To the Biotechnological Application Ofmentioning
confidence: 99%
“…Therefore, they play diverse roles as primary producers, predators, prey, symbiotic partners, and parasites in marine ecosystems (Jeong et al 2010, Holmes et al 2014, LaJeunesse et al 2018. Several dinoflagellate species are known to contain diverse biological materials of economic importance, such as omega-3 fatty acids, macrolides, essential amino acids, carotenoids, and toxins (Shimizu 1996, Mendes et al 2009, Onodera et al 2014, Lim et al 2018. For example, the heterotrophic dinoflagellate Crypthecodinium cohnii is used for commercial DHA production (Mobin and Alam 2017).…”
Section: Introductionmentioning
confidence: 99%